Analisis Kebutuhan Pengembangan Flipped Classroom pada Media Pembelajaran dengan Pendekatan Project Based Learning untuk Dikspespa Pendididkan di Kodiklatal - Okti Cahyandari; Murti Kusuma Wirasti; Dwi Kusumawardani (Jurnal Paedagogy, 2022)
This study aims to analyze learning needs related to the plan for developing flipped classroom learning on learning media subjects for the Dikspespa Pendidikan in Kodiklatal. This study combines the ADDIE development model with Research and Development (R & D), which is done by using a project-based learning approach. Initial analysis techniques are in the form of feasibility tests, field tests, and effectiveness tests. The data collected in this study were a qualitative descriptive approach. The research subjects were alumni from the Dikspespa of education and educators of the Dikspespa of education. The data were collected by interview, direct observation, and analysis of learning media subjects. The results of the study are in the form of a need for learning patterns that integrate technology in learning that can make learning more effective and efficient, especially to overcome time constraints in participating in learning activities, improve student learning outcomes while encouraging independence and motivating students who will later apply media subjects—learning in their assignments as instructors. Learning media subjects require much practice so that students have the experience to choose, create and use media; the right approach to use is project-based learning.